A New MicroRNA Expression Signature for Cervical Cancer. Issue 2 (February 2017) - Sun, Ping; Shen, Yong; Gong, Jiao-Mei; Zhou, Li-Li; Sheng, Jia-He; Duan, Fu-Jiao
Abstract : Background: Cervical cancer is the second most common cancer among women worldwide. The potential of microRNAs as novel biomarkers in cervical cancer is growing. Objectives: In this study, we investigated the functions and targets of miR-466 in cervical cancer tissues. Methods: Fresh cervical tissues were obtained from 157 patients with cervical cancer, cervical intraepithelial neoplasia (CIN), and healthy controls, and the tissues were immediately frozen in liquid nitrogen until use. The RNA was extracted and quantitative real-time polymerase chain reaction (PCR) was performed. Results: A total of 157 participants were summarized, including 56 patients with cervical cancer, 60 patients with CIN, and 49 healthy controls. The expression levels of miR-466 in cervical cancers (0.68) were higher than that in healthy controls (0.082) ( P < 0.01). The average fold changes of miR-466 in the patients with CIN group and people group were 0.28 and 0.082, respectively ( P < 0.01). It was a statistically significant difference in patients with lymph node involvement ( P = 0.022). However, the expression of miR-466 was not correlated with International Federation of Gynecology and Obstetrics stages, tumor size, or vascular invasion ( P = 0.506, P = 0.667, and P = 0.108, respectively). Conclusions: Our results indicate that the aberrant expression of miR-466 is closely associated with the occurrence and development of cervical cancer.